Exploring Students’ Learning Strategies and Teachers’ Teaching Strategies in English Reading Comprehension - Sutiadika, Miranda; Syahri, Indawan; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2023)
In the early stages of collecting articles based on the variables contained in the title, namely exploring student learning strategies and teacher teaching strategies in reading comprehension in junior high schools. This study reviews and synthesizes existing research and literature on student learning strategies and teaching strategies in reading comprehension. This study examines research that investigates various types of learning strategies used by students, such as meta-cognitive strategies, memory strategies, compensation strategies, affective strategies, cognitive strategies, and social strategies. In addition, this study also explores strategies used by teachers to improve students’ reading comprehension skills, including reciprocal strategies and question-answer relationships. Through a comprehensive literature review the researcher uses 8 articles as references to write the research, this study aims to provide insight into the effectiveness and impact of various learning strategies used by students and the strategies used by teachers in teaching reading comprehension.